STUDYING AN ADJECTIVE AS A WAY TO REVEAL THE AESTHETIC VALUE OF A FICTIONAL BOOK IN THE FIRST GRADE (EDUCATION IN THE 21ST CENTURY, 2023)
Starting from the pre-alphabetic period in school, students start studying adjectives as words modifying nouns through practical exercises, which enriches students’ vocabulary with attributive words that are used in the form of in form of synonyms and antonyms as “friendly” and “opponent” concepts.The comparative teaching of adjectives with the help of antonyms is further uses the peculiarities of two categories of modifying words. A group of words modify an object, while another group modifies an action, answering the questions “What kind of?” and “How” respectively.Analytical learning of attributive words (sentence-word combination-word) is especially important.The main purpose of teaching adjectives is to reveal the aesthetic value of a fictional book read. As a result, students enrich their vocabulary and develop their speech, which stimulates an individual’s visual thinking. Modern teachers use a combination of inductive and deductive teaching methods. The latter develops the ability and skill to form coherent speech through phrases made of a noun and an adjective, and ensure the ability to freely communicate and express one’s emotions, and, as a result, gives an opportunity to build interpersonal relationships.In elementary school, theoretical knowledge is taught to students in parallel with reading works of fiction. Based on this, teachers use linguisic-logical tasks to teach linguistic materials mainly by the method of ‘spiral’ repetition.
Keywords: Keywords: words modifying nouns, pre-alphabetic period, attributive words, comparative teaching, coherent speech.